CAG Repeats Within the Non-pathological Range in the HTT Gene Influence Personality Traits in Patients With Subjective Cognitive Decline: A 13-Year Follow-Up Study - Moschini, Valentina; Mazzeo, Salvatore; Bagnoli, Silvia; Padiglioni, Sonia; Emiliani, Filippo; Giacomucci, Giulia; Morinelli, Carmen; Ingannato, Assunta; Freni, Tommaso; Belloni, Laura; Ferrari, Camilla; Sorbi, Sandro; et al. (Frontiers in Psychiatry, 2022)
Objective: HTT is a gene containing a key region of CAG repeats. When expanded beyond 39 repeats, Huntington disease (HD) develops. HTT genes with less than 35 repeats are not associated with HD. The biological function of CAG repeat expansion below the non-pathological threshold is not well understood. We aimed to evaluate the effect of CAG repeat length on personality traits and mood in patients with subjective cognitive decline (SCD). Methods: We included 54 patients with SCD. All patients underwent an extensive neuropsychological battery at baseline, APOE genotyping and analysis of HTT alleles. We used the Big Five Factors Questionnaire (BFFQ) and Hamilton Depression Rating Scale respectively to assess personality traits of patients and depression at baseline. Patients who did not progress to Mild Cognitive Impairment (MCI) had at least 5-year follow-up time. Results: In the whole sample, CAG repeat number in the shorter HTT allele was inversely correlated with conscientiousness (Pearson=-0.364, p=0.007). There was no correlation between HDRS and CAG repeats. During the follow-up, 14 patients (25.93% [95% C.I.=14.24-37.61]) progressed to MCI (MCI+) and 40 (74.07% [95% C.I.=62.39-85.76]) did not (MCI–). When we performed the same analysis in the MCI+ group we found that: CAG repeat length on the shorter allele was inversely correlated with energy (Pearson= 0.639, p=0.014) and conscientiousness (Pearson=-0.695, p=0.006). CAG repeat length on the longer allele was inversely correlated with conscientiousness (Pearson=-0.901, p<0.001) and directly correlated with emotional stability (Pearson=0.639, p=0.014). These associations were confirmed also by multivariate analysis. We found no correlations between BFFQ parameters and CAG repeats in the MCI– group. Discussion: Personality traits and CAG repeat length in the intermediate range have been associated with progression of cognitive decline and neuropathological findings consistent with AD. We showed that CAG repeat lengths in the HTT gene within the non-pathological range influence personality traits.